2015
DOI: 10.1371/journal.pone.0141431
|View full text |Cite
|
Sign up to set email alerts
|

Body Acceleration as Indicator for Walking Economy in an Ageing Population

Abstract: BackgroundIn adults, walking economy declines with increasing age and negatively influences walking speed. This study aims at detecting determinants of walking economy from body acceleration during walking in an ageing population.Methods35 healthy elderly (18 males, age 51 to 83 y, BMI 25.5±2.4 kg/m2) walked on a treadmill. Energy expenditure was measured with indirect calorimetry while body acceleration was sampled at 60Hz with a tri-axial accelerometer (GT3X+, ActiGraph), positioned on the lower back. Walkin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 44 publications
2
17
0
Order By: Relevance
“…The results of a previous study suggested that subjects with different walking economy produce different acceleration outputs [ 17 ]. This might have implications on the relationship between PAL and activity counts.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The results of a previous study suggested that subjects with different walking economy produce different acceleration outputs [ 17 ]. This might have implications on the relationship between PAL and activity counts.…”
Section: Discussionmentioning
confidence: 99%
“…The population included 35 subjects from a previous study and 7 subjects with similar characteristics [ 17 ]. All 42 healthy subjects (19 males and 23 females) aged between 51 and 84 years (mean body mass index 25.6 kg/m 2 [SD 2.6]) were recruited by advertisements in local newspapers ( Table 1 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The tests were performed on a level and clear 30-m corridor, with 1.5-m space for acceleration and deceleration, and without encouraging words. Gait speed between 0.90-1.42 m/s has been considered adequate for the walking economy during the ageing process [18,19]. Berg Balance Scale validated to Brazilian Portuguese [20] was used to assess functional balance performance; and was based on 14 questions with answers ranging from 0 to 4 points.…”
Section: Performance Testsmentioning
confidence: 99%
“…In this study, surface EMG was used to measure the muscle activity which indicates how a rider's dynamic trunk alignment improves from horseback riding. Exploratory data analysis was performed using accelerometers, which is a popular method in the kinesiological field [ 14 , 15 , 16 ]. In this study, we measured acceleration and angular velocity simultaneously, enabling analysis of the rectilinear and rotational motions of the horse and rider to elucidate the aforementioned mechanism.…”
Section: Introductionmentioning
confidence: 99%